2022
DOI: 10.1002/ange.202215600
|View full text |Cite
|
Sign up to set email alerts
|

Monolithic Phosphate Interphase for Highly Reversible and Stable Zn Metal Anode

Abstract: Zinc metal battery (ZMB) is promising as the next generation of energy storage system, but challenges relating to dendrites and corrosion of the zinc anode are restricting its practical application. Here, to stabilize Zn anode, we report a controlled electrolytic method for a monolithic solid‐electrolyte interphase (SEI) via a high dipole moment solvent dimethyl methylphosphonate (DMMP). The DMMP‐based electrolytes can generate a homogeneous and robust phosphate SEI (Zn3(PO4)2 and ZnP2O6). Benefiting from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…It was reported that in typical aqueous metal-ion batteries, the difference in the redox properties of different anions will have impact on the electrochemical behaviors of electrode reactions. 6,32 Considering the ability of different anions to coordinate with metal cations, 31,50 we firstly studied the Mn anode in three most commonly used Mn-based electrolytes, i.e. , manganese sulfate (MnSO 4 ), manganese chloride (MnCl 2 ) and manganese nitrate (Mn(NO 3 ) 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that in typical aqueous metal-ion batteries, the difference in the redox properties of different anions will have impact on the electrochemical behaviors of electrode reactions. 6,32 Considering the ability of different anions to coordinate with metal cations, 31,50 we firstly studied the Mn anode in three most commonly used Mn-based electrolytes, i.e. , manganese sulfate (MnSO 4 ), manganese chloride (MnCl 2 ) and manganese nitrate (Mn(NO 3 ) 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…S2, ESI†). 13,49–51 This provides great opportunities for the Mn/Mn 2+ reactions to occur in some engineered electrolytes. Therefore, it is theoretically feasible to construct an AAMB with a theoretical potential of 2.42 V.…”
Section: Introductionmentioning
confidence: 99%
“…Presently, it is acknowledged that the development of zinc anode is impeded by numerous issues, originating from dendrites formation, hydrogen evolution, corrosion and passivation, and their interactive influence. 39,40…”
Section: Mechanism and Challenges Of Zinc Anodementioning
confidence: 99%
“…The corresponding voltage-capacity profiles for G) additive-free and H) 1% Butandiol electrolyte cells at 2 mA cm −2 and 2 mAh cm −2 with 10 μm Zn. I) The comparison of cumulative plated capacity, electrolyte to capacity (E/C) ratio, Zn utilization, separator thickness, and additive concentration with other reported low-concentration organic additives [33][34][35] and in situ SEI [22,25,36,37] constructing electrolyte additives.…”
Section: % Butanediol Additive For Highly Stable Zinc Anode Cyclingmentioning
confidence: 99%
“…Nonetheless, the remarkable long-term zinc cycling reversibility exhibited under high Zn utilization, low E/C ratio, and thin separator, achieved with the low concentration (1 vol%) of the butanediol additive, exceeds the performance of nearly all previous additive-based research works. [22,25,[33][34][35][36][37]…”
Section: % Butanediol Additive For Highly Stable Zinc Anode Cyclingmentioning
confidence: 99%